Accessibility Analysis of Websites of Provincial Governments in Indonesia - Vinna Rahmayanti Setyaning Nastiti; Amelia Deastu; Gita Indah Marthasari (Universitas Muhammadiyah Malang, 2022)
Web accessibility means that people with disabilities can use, navigate, and interact with the website. The World Wide Web Consortium (W3C) has provided important guidelines on web accessibility known as the Web Content Accessible Guidelines (WCAG). The Indonesian government encourages the use of new media, namely website, via Presidential Instruction number 3 of 2003 concerning the National Policy and Strategy for e-government development, which mandates every government agency to build a website. In the previous study, the tools used had limitations and were unable to complete the websites evaluation. Therefore, in this study, WCAG 2.0 standard was applied to analyze the websites of provincial governments in Indonesia. Two accessibility evaluation tools were employed, namely TAW and aXe. In addition, for data analysis and interpretation, descriptive statistics and normality tests were applied. The results showed that the most common violation was found in perceivable principle. It was expected that the findings of this study could provide insight and recommendation for web developers working on provincial government website in Indonesia.